Avaliação da satisfação do aluno com deficiência no ensino superior: estudo de caso da UFSCar - Guerreiro, Elaine Maria Bessa Rebello (Universidade Federal de São Carlos, 2011)
The increasing number of disabled students in higher education has raised issues that were, in the past, focused on basic education. Those issues create now an urgent need in higher education for physical infrastructure, pedagogical practices, technological resources and interpersonal relationships. Studies have been done on urban, architectonic, and attitudinal barriers, and also on the difficulties of access and permanency, reservation of vacancies and other issues regarding the inclusion of disabled people in higher education. Although some studies have shown the satisfaction of the student in higher education, the specific and necessary issues of the disabled student are still absent. Considering this, the objective of this research is to understand the level of satisfaction of the disabled student, regarding access and retention, through an instrument that was constructed for this purpose. For this, a higher education institution was chosen, in which the necessary characteristics for testing the instrument were present. Within this objective, it was proposed to identify the profile of this population, the level of satisfaction regarding the offered physical and operational structures, the level of satisfaction and attitude towards obstacles, as well as knowledge of legislation on accessibility and the NBR 9050/2004. This is a quantitativequalitative (emphasizing the first), exploratory, correlational, transversal study. The sample consisted of eighteen students: eight of them were visually disabled; six were physically disabled; three were hearing disabled; and one had learning difficulties. The constructed instrument was named Scale of Satisfaction and Attitudes of Disabled People SSA. As a result of the sample size, the techniques were used towards an exploratory rather than an inferential sense; therefore, the findings are restricted. It was verified that the average figures of the groups differ in a statistically significant way (p=0.065) by the Friedman Test, indicating that there are differences among structural, operational and psycho affective satisfaction, and the attitudes towards obstacles, in the studied group, at 90% certainty. Regarding the Structural factor, 50% of the sample tended to satisfaction, whereas the others tended to dissatisfaction and satisfaction with 25% on each side. In the Operational factor, 25% of the ones who answered to the items were dissatisfied, 50% tended to dissatisfaction and 25% were satisfied. In the Psycho Affective factor, 25% tend to satisfaction and 75% are satisfied. Regarding the Attitude towards obstacles, 25% showed certain neutrality or preference for omission, whilst 75% had a positive attitude. Regarding knowledge of legislation on accessibility and the norm NBR 9050/2004 of ABNT, it was observed that the disabled students who participated in the research that had no prior knowledge of the norm (approximately 60%) knew very little about the legislation on accessibility. The opposite is true for those who knew about the norm, that is, all of these knew the legislation on accessibility very well, and they also had a lower level of structural satisfaction. The participants with visual disability showed more knowledge regarding the legislation and the NBR 9050/2004. The students with visual and physical disabilities showed lower levels of satisfaction for the Structural factor, and the students with hearing disabilities showed lower levels for the Operational factor, especially when communicating with teachers and while in classes. However, the levels for the Psycho Affective and Attitude factors were within the range of satisfaction which compensates the low levels for Structural and Operational factors. Therefore, these findings allow us to state that the application of an instrument that measures the satisfaction of the disabled student in higher education is feasible and useful, in order to consider the direction the university is taking, when it comes to the access and the retention of these students.
Keywords: Educação especial; Acessibilidade; Pessoas com deficiências; Inclusão escolar; Inclusão social; Special education; Satisfaction; Accessibility; Higher education; Students with disabilities; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL